The effect of using all of my style of learning (interactive - Prince) to learn the skill of rolling back on the balance beam - Kadhim, Bushra; Shihab, Huda (Journal of Physical Education, 2007)
Traditional teaching methods currently followed are no more capable of keeping up with recent educational philosophies, which focus on using methods that make the student more reacting in the educational process by letting him join in placing the subjects needed for studying, and finding the situation where the student is more positive and active. So, the researchers have come to executing this research in order to know the effect of using the two learning means (reciprocal – imperative) in learning the back-rolling skill on the balance beam to follow up on the new direction in using the new methods in learning sports skills. The research aimed at introducing the effect of using the two learning methods (reciprocal – imperative) on the back-rolling skill on the balance beam on a performance level by girl students, and showing the most effective means on the skill performance level. The researchers have used the experimental method due to its convenience with the nature of this study. The research specimen consisted of (40 students / girls) from the third stage, and the duration of this research was two months. An arbitration committee formed of teachers corrected the movement. The study concluded that the reciprocal method in teaching the back-rolling skill on the balance beam surpassed the traditional method